Pengaruh Lingkungan Kerja, Stres Kerja, dan Budaya Organisasional Terhadap Kepuasan Kerja Karyawan: Indonesia - Wina Anggraini; Ignatius Soni Kurniawan; Eko Yulianto (Universitas Hamzanwadi, 2025)
This study aims to analyze the influence of the work environment, work stress, and organizational culture on employee job satisfaction. The approach used in this study is quantitative, with the application of the Partial Least Square-Structural Equation Modeling (PLS-SEM) method, which was analyzed using SmartPLS 3 software. A total of 70 respondents participated in completing the questionnaire distributed offline. The research findings indicate that the work environment has a negative but non-significant influence on job satisfaction, work stress has a significant negative influence on job satisfaction, and organizational culture has a significant positive influence on job satisfaction. The implications of this research emphasize the importance of managing work stress and improving organizational culture in managing job satisfaction.